UPAYA MENINGKATKAN KUALITAS HASIL PEMBELAJARAN SISWA TERHADAP MATERI PESAWAT SEDERHANA KELAS V SD NEGERI NGAWEN - -, Suyitno (Universitas Muria Kudus, 2015)
The purpose of this study was to determine whether there is science learning outcomes on a simple plane Ngawen Elementary School fifth grade, Sub Cluwak, Pati regency. In the second semester of the school year 2014/2015 This research is a classroom action research (PTK) to solve the problem of whether the experiment (PAKEM) can improve student learning outcomes. PTK lasted until 3 cycles, each cycle consisting of (1) planning or planning, (2) the act or acting, (3) observation or observing, and (4) reflection or reflecting. The fourth relationship was regarded as one cycle. Collection and use of technical documentation, observation and testing, data collection tools in the form of the document journal learning, observation sheet and test items. Data analysis using descriptiveKomperatif by comparing the baseline of the first cycle data and the data of the second cycle followed by reflection. Results of a study of 25 students learning standards set minimum completeness 75, meaning students who have achieved a grade of 75 otherwise been completed. Furthermore, students who achieve a value of less than 75 otherwise unresolved in learning and need to get improvements in learning. From the research results at the end of the lesson formative tests turned out of 25 students who achieve grades above completeness only 9 students, if diprosentase students who otherwise completed only 35%. So unresolved classically reaches 65%. The conclusion of this experimental study (PAKEM) can improve the quality of student learning outcomes to the material plane Simple Ngawen Elementary School fifth grade, Sub Cluwak, Pati regency, through the medium of learning and teaching aids that characterized the student environment.